OF HIGHLY SKILLED RALLY RACERS OPTIMIZATION OF PSYCHOPHYSICAL PREPARATION (Multidisciplinary Journal of Science and Technology, 2024)
The article examines the problems of psychophysical training in motor sports, the peculiarities of competitive activity. The most important areas are the selection of criteria and optimization of rallying training. The improvement of the training system in this sport has been studied